Effect of inlet pipe design on self-cleaning ability of a circular tank in RAS - Zhang, Yuji; Yang, Xu; Hu, Jiajun; Qu, Xiaoyu; Feng, Dejun; Gui, Fukun; Zhu, Fang (Frontiers in Marine Science, 2023)
To study the characteristics of waste collection and flow field distribution in circular recirculating aquaculture tanks under different inlet modes, this research investigated the effect of the inlet pipe deployment distance d (the distance between the stream tube hole and the tank wall) and the inlet pipe deployment angle α (the acute angle between the inlet direction and the nearest tank wall) on the self-cleaning ability of the circular aquaculture tank under single-inlet and dual-inlet pipe drive modes. First, the Particle Image Velocimetry (PIV) technique was employed to measure the flow field, analyze the hydrodynamic characteristics of the culture tank, and quantify the effect of the inlet pipe setting mode on the hydrodynamic characteristics of the waste collection of the circular aquaculture tank. Then, the influential mechanism of the inlet pipe setting mode on the waste collection and the hydrodynamic characteristics of the aquaculture tank were explored by analyzing the flow pattern of the flow field in the aquaculture tank and the hydrodynamic characteristic indicators, such as the average flow velocity vavg, the uniformity coefficient of water flow DU50, and the water resistance coefficient Ct. The results of the comprehensive waste collection experiments and flow field measurement experiments indicate that the hydrodynamic characteristics of the waste collection in the aquaculture tank are optimal in the dual inlet pipe mode with d=1/4 r and α=20° 30°. Also, the waste collection in the single inlet pipe mode has similar optimal hydrodynamic characteristics under d=1/4 r, α=20° 30° and d=1/2 r, α=0° 10°. At the same flow rate, the discharge velocity in the single inlet pipe mode is significantly greater than that in the dual inlet pipe mode, and the hydrodynamic characteristics of the waste collection are better. Therefore, in actual circulating water aquaculture production, this paper recommends setting the inlet pipe of a similar aquaculture tank to the single inlet pipe mode and setting the inlet pipe with d=1/4 r, α=20° 30° or d=1/2 r, α=0° 10°, thus improving the waste collection characteristics of the aquaculture tank. The study results also provide a reference for the adjustment of the inlet pipe setting mode in real applications.